Exposure to Literary Fiction Is Associated With Lower Psychological Essentialism - Castano, Emanuele; Paladino, Maria Paola; Cadwell, Olivia G.; Cuccio, Valentina; Perconti, Pietro (Frontiers in Psychology, 2021)
We investigated the impact of exposure to literary and popular fiction on psychological essentialism. Exposure to fiction was measured via the Author Recognition Test, which allows us to separate exposure to authors of literary and popular fiction. Psychological essentialism was assessed via the discreteness subscale of the psychological essentialism scale in Study 1, and via the three subscales of the same scale (discreteness, informativeness and biological basis) in Study 2. Study 2 was pre-registered. Results showed that exposure to literary fiction negatively predicts the three subscales. The results emerge controlling for political ideology, a variable that is commonly associated with psychological essentialism, and level of education.